P.E.H. HAIR: The Atlantic Slave Trade and Black Africa; y C. DUNCAN RICE: The rise and fall of Black Slavery - Martínez Carreras, José U. (Cuadernos de Historia Moderna y Contemporánea, 1982)
Sin resumen